2021
DOI: 10.1002/pen.25640
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization and modeling stress relaxation behavior of acrylic–polyurethane‐based graft‐interpenetrating polymer networks

Abstract: The stress relaxation behavior of acrylic-polyurethane (PU)-based graftinterpenetrating polymer networks (IPNs) was characterized via dynamic mechanical analysis (DMA) and modeled using finite element method (FEM) analysis. Stress relaxation of glassy IPN specimens was experimentally studied under flexural testing, while rubbery IPN specimens were tested in tension. The effects of varying the styrene content in the acrylic copolymer phase, compatibility of the two phases in IPNs, and changing the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The internetwork entanglements and cross-linked structure of the participating polymers were eternal and prevent the material from fracture. Entanglements and cross-linked structure leaded to forced compatibility between the two polymers and thus generated the arranged structure within the network structure. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The internetwork entanglements and cross-linked structure of the participating polymers were eternal and prevent the material from fracture. Entanglements and cross-linked structure leaded to forced compatibility between the two polymers and thus generated the arranged structure within the network structure. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…A well-constructed preparation–structure–properties model can be used for performance prediction, structure control, and process optimization. , Over the past few years, several models describing the application properties have been developed. For instance, Wen et al predicted the glass transition temperature of polyimide via all-atom molecular dynamic simulations or machine-learning algorithms .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods for preparing composite hydrogel materials, interpenetrating polymer network (IPN) is generally considered to be one of the most effective methods for imparting high-strength mechanical properties as well as controllable swelling and degradation to the hydrogel materials. [13,14] IPN is commonly composed of two polymer networks, whose molecular chains interpenetrate each other, or one of the networks is cross-linked and polymerized in the matrix of the other network. [15,16] It is reported that the IPN hydrogel system has significant fracture toughness and large compressive strain in comparison with traditional hydrogels.…”
Section: Introductionmentioning
confidence: 99%